WALSH, KORT FORTALT - Reitan, Rolf (K&K - Kultur og Klasse, 2013)
RICHARD WALSH: A CONTEXTUAL EXPOSITION OF BASIC TENETS | This essay is an attempt to reconstruct the logical structure of Walsh’s argument in “The pragmatics of fictionality” (Chapter 1 of The Rhetoric of Fictionality). Its main focus is on the implications of Walsh’s criticism of Fictional Worlds Theory and the issue of fictional reference, and on the relation between the rhetoric of fictionality and narratology.